L. Tolstoy's plays in Lithuania (1887-1918) - B. Masionienė (Literatūra (Vilnius), 1974)
There is 110 special work on the dissemination of L. Tolstoy's plays in Lithuania and their influence on the Lithuanian national playwriting and theatre. This subject, however, is of interest for literary critics. The article deals with the problem of translation of L. Tolstoy's drama works and presents some notes on their life in Lithuanian theatre in the period of 1887-1918.